2018
DOI: 10.1016/j.adolescence.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

School effectiveness and students' future orientation: A multilevel analysis of upper secondary schools in Stockholm, Sweden

Abstract: Introduction: Future orientation (FO) refers to individuals' beliefs and feelings about their future. Earlier research has primarily investigated correlates of FO at the individual and family level, but it seems likely that FO is also shaped by other central agents or institutions, such as the school. Earlier studies have found positive associations between "school efectiveness" and student performance, and negative associations in relation to e.g., bullying, delinquency, and health risk behaviors. The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
5
22
0
3
Order By: Relevance
“…Yet another pathway could be students' future orientation. A previous study which was based on the same data material as the current study reported that a strong school ethos, as rated by teachers, was linked with an optimistic future orientation among the students [25]. A pessimistic future orientation, by contrast, has been connected with a greater likelihood of engaging in risk gambling [27] as well as other health risk behaviours [26].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Yet another pathway could be students' future orientation. A previous study which was based on the same data material as the current study reported that a strong school ethos, as rated by teachers, was linked with an optimistic future orientation among the students [25]. A pessimistic future orientation, by contrast, has been connected with a greater likelihood of engaging in risk gambling [27] as well as other health risk behaviours [26].…”
Section: Discussionsupporting
confidence: 57%
“…Still another pathway may be via students' future orientation. A strong school ethos has been shown to be connected with a more optimistic future orientation among the students [25]. Feelings of hopelessness and a sense of a lack of future prospects may in turn make individuals more prone to risk behaviours.…”
Section: Background and Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…It was seen that positive future orientation can enhance student's functioning in school. It was also noted that student's school setting boost their future beliefs that can be done through progressive student-teacher relationship, educational motivation and accomplishment (Alm, Låftman, Sandahl & Modin, 2019). Previous studies confirmed the findings of the current research as the time perspectives play a vital role in determining the moral concerns (Agerström & Björklund, 2009) and (Eyal, Liberman & Trope, 2008).…”
Section: Discussionsupporting
confidence: 85%